2008
DOI: 10.1088/0004-6256/136/2/725
|View full text |Cite
|
Sign up to set email alerts
|

Minor Planet 2008 Ed69 and the Kappa Cygnid Meteor Shower

Abstract: Until recently, the kappa Cygnids (IAU#12) were considered an old shower, because the meteors were significantly dispersed in node, radiant, and speed, despite being 28-38• inclined. In 1993, an outburst of kappa Cygnids was observed, which implied that this meteoroid stream was relatively young, instead. At least some dust was still concentrated in dust trailets. Until now, no active comet parent body was known, however, and the wide 22• dispersion of nodes was difficult to explain. This work reports that a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 17 publications
3
22
0
Order By: Relevance
“…It is beyond the scope of this paper to give a complete review of all relevant studies. We could describe here those by Wu & Williams (1992, 1993, Williams et al (2004b,a), Jones et al (2006), Porubčan et al (2006), Babadzhanov et al (2008), Jenniskens & Vaubaillon (2008), Wiegert et al (2009), Christou & Vaubaillon (2010), Williams & Ryabova (2011), Babadzhanov et al (2013), and other authors. A review of the techniques used for the modeling of meteoroid streams in the solar system was recently given by Vaubaillon et al (2015).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…It is beyond the scope of this paper to give a complete review of all relevant studies. We could describe here those by Wu & Williams (1992, 1993, Williams et al (2004b,a), Jones et al (2006), Porubčan et al (2006), Babadzhanov et al (2008), Jenniskens & Vaubaillon (2008), Wiegert et al (2009), Christou & Vaubaillon (2010), Williams & Ryabova (2011), Babadzhanov et al (2013), and other authors. A review of the techniques used for the modeling of meteoroid streams in the solar system was recently given by Vaubaillon et al (2015).…”
Section: Introductionmentioning
confidence: 78%
“…Of the works mentioned in Sect. 1, the P-R effect was taken into account only by McIntosh & Jones (1988) and in the works coauthored by Vaubaillon (Jenniskens & Vaubaillon 2008;Wiegert et al 2009;Christou & Vaubaillon 2010), in which the method of sofisticated stream modeling (Vaubaillon 2004;Vaubaillon et al 2005) was used. Recently, the P-R drag was considered by Jakubík & Neslušan (2015) in their study of the Phaethon's meteoroid stream.…”
Section: Stream Modelingmentioning
confidence: 99%
“…The χ-Orionids are associated with asteroid 2008XM1 (Madiedo et al 2013). Other associations have been discussed by Jenniskens & Vaubaillon (2008) and Trigo-Rodriguez et al (2007.…”
Section: Introductionmentioning
confidence: 99%
“…Since the review of Porubcan et al (2004), there have been a number of advances, the most notable perhaps being NEO 2003EH1 and its association Article published by EDP Sciences with the Quadrantid shower (Jenniskens 2004;Williams et al 2004), while Babadzhanov & Williams (2007) found meteor showers associated with 2000PG3 andBabadzhanov et al (2008b) found that 4 NEOs were related to the Piscids meteoroid stream. Jenniskens & Vaubaillon (2008) showed that the Kappa Cygnids had a similar origin. An overview of the topic is given in Jenniskens (2008).…”
Section: Introductionmentioning
confidence: 99%
“…The problem of distinguishing between a dormant comet and an asteroid is not confined to the NEO population, as discussed for example in the outer asteroid belt by Fitzsimmons et al (1994), Williams (1997). Near the end of their lives, a comet nucleus may also fragment, leaving several small objects on very similar orbits to each other (Jenniskens & Vaubaillon 2008), none showing any signs of cometary activity and all classed as asteroids.…”
Section: Introductionmentioning
confidence: 99%